Analisis Implementasi Kebijakan Perlindungan Anak Korban Kekerasan Seksual di Indonesia Dalam Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual (UU TPKS) [Analysis of the Implementation of Policies for the Protection of Child Victims of Sexual Violence in Indonesia Under Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS)] - Pratama, Ardian; Mandala, Opan Satria; Rahmatyar, Ana (Indonesia Berdaya, 2025)
Sexual violence against children is a serious crime that requires effective and comprehensive legal protection. The implementation of Law No. 12 of 2022 on the Crime of Sexual Violence (UU TPKS) faces significant challenges, including difficulties in case identification and reporting, lack of public awareness, and limited resources. The research method used in this research is normative on laws and regulations and literature related to sexual violence against children. The result of the research is that the implementation of Law Number 12 of 2022 on Criminal Acts of Sexual Violence (UU TPKS) can provide effective legal protection for child victims of sexual violence through increasing public awareness, strengthening the law enforcement system, and providing quality protection services. However, this implementation still faces challenges such as difficulties in case identification and reporting, weak implementation of the law, limited resources, and difficulties in accessing services. Cooperation between the government, child protection agencies, police, the justice system, and communities is needed to overcome these challenges and provide better protection for child victims of sexual violence. Abstrak. Kekerasan seksual terhadap anak merupakan kejahatan serius yang memerlukan perlindungan hukum yang efektif dan komprehensif. Implementasi Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual (UU TPKS) menghadapi tantangan signifikan, termasuk kesulitan identifikasi dan pelaporan kasus, kurangnya kesadaran masyarakat, dan keterbatasan sumber daya. Metode penelitian yang digunakan penelitian ini adalah normatif terhadap peraturan perundang-undangan dan literatur terkait kekerasan seksual terhadap anak. Hasil penelitian adalah Implementasi Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual (UU TPKS) dapat memberikan perlindungan hukum yang efektif bagi anak korban kekerasan seksual melalui peningkatan kesadaran masyarakat, penguatan sistem penegakan hukum, dan penyediaan layanan perlindungan yang berkualitas. Namun, implementasi ini masih menghadapi tantangan seperti kesulitan identifikasi dan pelaporan kasus, lemahnya penerapan UU TPKS, keterbatasan sumber daya, dan kesulitan akses layanan. Kerjasama antara pemerintah, lembaga perlindungan anak, kepolisian, sistem peradilan, dan masyarakat diperlukan untuk mengatasi tantangan ini dan memberikan perlindungan yang lebih baik bagi anak-anak korban kekerasan seksual.